2017
DOI: 10.5455/msm.2017.29.176-181
|View full text |Cite
|
Sign up to set email alerts
|

Budget Impact of Introducing Linagliptin into Bosnia and Herzegovina Health Insurance Drug Reimbursement List in 2016-2018

Abstract: Introduction:Diabetes is reaching epidemiological scales worldwide. Beside health implications diabetes bears significant financial impact on health systems. Different treatment options aiming to prevent diabetes complications are available. Dipeptidyl-peptidase-IV (DPP-4) inhibitors like linagliptin are usually add-on therapy to metformin in order to achieve glycemic control. Expenditure for oral antidiabetic medicines in Bosnia and Herzegovina (B&H) is low accounting for only 2.53% of the total drug market e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 17 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…IDF Diabetes Atlas estimated that in 2017 there were 451 million people with diabetes worldwide and it is expected that this number will increase to 693 million by 2045 (1). It is estimated by the diabetes associations in Bosnia and Herzegovina (B&H) that more than 220.000 people or 5,1% of population suffer from diabetes and majority are patients with type 2 diabetes (2). The main goal of diabetes treatment is to prevent or delay complications and maintain quality of life as stated in the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) Consensus Report published in 2018 (3).…”
Section: Introductionmentioning
confidence: 99%
“…IDF Diabetes Atlas estimated that in 2017 there were 451 million people with diabetes worldwide and it is expected that this number will increase to 693 million by 2045 (1). It is estimated by the diabetes associations in Bosnia and Herzegovina (B&H) that more than 220.000 people or 5,1% of population suffer from diabetes and majority are patients with type 2 diabetes (2). The main goal of diabetes treatment is to prevent or delay complications and maintain quality of life as stated in the American Diabetes Association (ADA) and the European Association for the Study of Diabetes (EASD) Consensus Report published in 2018 (3).…”
Section: Introductionmentioning
confidence: 99%
“…The discounting rate was not always clearly reported in the included BIA studies. Four studies reported the discounting rate ranging from 3 to 5% (16,(23)(24)(25), eight studies (11,15,(17)(18)(19)(20)(21)27) did not consider the discounting rate in compliance with the ISPOR Task Force guidelines (7). Meanwhile, six studies (10, 12-14, 22, 26) did not mentioned the discounting rate in the articles.…”
Section: Methodology and Budget Results Of Biasmentioning
confidence: 99%
“…Condition-related costs included adverse event costs and complication costs. Seven studies only calculated treatmentrelated costs only (10,(13)(14)(15)(21)(22)(23). Eleven studies took into account both treatment-related costs and condition-related costs (11,12,(16)(17)(18)(19)(20)(24)(25)(26)(27), of which nine studies considered the cost of hypoglycemia which was further classified into minor and severe hypoglycemia (11,12,16,18,20,(24)(25)(26)(27), six studies considered the cost of diabetes-related complications (11,16,17,19,25,27) (mainly including myocardial infarction (MI), stroke, heart failure, heart disease) and only one took the cost of adverse event (including dizziness, vomiting, fatigue and loss of appetite) into account (12).…”
Section: Methodology and Budget Results Of Biasmentioning
confidence: 99%
See 2 more Smart Citations